Which Clause Type do You Use in Your Conversation? - Suparjan Suparjan (Jurnal Visi Ilmu Pendidikan, 2015)
The objective of this article is to discuss the classification of clause type in English Grammar commonly used for either formal or informal conversation. It cannot be avoided that people always tell, ask, command, request and perform other acts for their daily communicative purpose. These kinds of acts are commonly referred as Clause Type. Basically, there are four terms of clause type in English namely declarative, interrogative, exclamative, and imperative. Those terms of clause type are employed to accomplish different communicative intentions. Moreover, knowing Clause type in English may contribute a clear understanding during having English intercourse with the speakers.